Inflation Persistence or the Protracted Effects of Commodity Price Changes? - Wolfgang Pollan (Austrian Institute of Economic Research (WIFO), 2013)
This paper explores the question to what extent non-domestic factors provide an explanation of US inflation over the last three decades. Are lagged dependent variables - traditionally interpreted as proxies for inflation expectations - just proxies for oil and commodity prices? To answer this question a simple Phillips curve, which includes energy prices, is estimated for the USA. The results show that crude oil prices, which basically are world market prices, have exerted a strong influence on inflation, while the effects of domestic factors, such as the unemployment rate, have become weaker. These findings help to resolve a puzzle of recent years: given the sharp rise in unemployment, why has inflation not slowed down as much as predicted by the traditional Phillips curve analysis? Furthermore, the empirical results assign a much feebler role to expectations in the inflation process; if indeed inflation is a global phenomenon, the task of controlling inflation expectations by monetary policy may not be as crucial as implied by central banks statements pointing to the importance of anchoring inflation expectations. Are the actions of central banks nothing more than a sideshow?
Keywords: 330; Commodity prices; expectations; inflation; monetary policy; Phillips Curve; Inflationsrate; Inflationserwartung; Energiepreis; Phillips-Kurve; USA